2021
DOI: 10.1016/j.cellsig.2021.110148
|View full text |Cite
|
Sign up to set email alerts
|

SPIB acts as a tumor suppressor by activating the NFkB and JNK signaling pathways through MAP4K1 in colorectal cancer cells

Abstract: BackgroundColorectal cancer (CRC) is one of the major cancers in the world. Spi-B Transcription Factor (SPIB) is one member of the E-twenty-six (ETS) transcription factor family. Previous studies have shown that the expression of SPIB is down-regulated in human colorectal cancer tissues. However, its biological function in colorectal cancer cells is not reported. The purpose of our study is to explore the biological function and related mechanism of SPIB in colorectal cancer cells, to provide reference for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…These results are consistent with previous studies that SPIB is essential in protective humoral immunity [4]. In addition, SPIB has been associated with tumor suppression via NFkappa B signaling pathway [8], consistent with our study findings.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with previous studies that SPIB is essential in protective humoral immunity [4]. In addition, SPIB has been associated with tumor suppression via NFkappa B signaling pathway [8], consistent with our study findings.…”
Section: Discussionsupporting
confidence: 94%
“…An increasing body of evidence from recently published studies suggests that SPIB plays an important role in tumor development. For instance, SPIB reportedly exerts an inhibitory effect in colorectal cancer cells by activating NFkB and JNK signaling through MAP4K1 [ 8 ] and promotes tumor-associated macrophage (TAM) recruitment by enhancing the expression of CCL4 in lung cancer [ 9 ]. Moreover, SPIB plays an important role in the abnormal switch reorganization of ABC DLBCL [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subnetwork A was the primary driver behind the previously noted thymus-specific high expression of inflammatory response pathway regulons, connecting the interferon response factor regulons IRF1, IRF7, IRF8, IRF9 with an even larger number of STAT family regulons ( STAT5A, STAT3, STAT2 and STAT1), NF- family subunit regulons NFKB1, NFKB2 and RELB, and the NF- SPIB 45 , HIVEP1 46 . Interferon (IFNs) are a family of cytokines known to induce cell intrinsic programs with antiviral, immunomodulatory and antiproliferative properties 47 .…”
Section: Resultsmentioning
confidence: 94%
“…The high expression of FOXJ1 was found to be associated with better disease-free survival, and it may be a good prognostic factor for BRCA (41). Little is known about the role of SPIB in BRCA, but research has shown that it exerts anti-cancer effects in colorectal cancer (42). LEF1 is regarded as a potential biomarker for the metastasis of BRCA (43).…”
Section: Discussionmentioning
confidence: 99%